Hyponatremia in Children With Bacterial Meningitis - Zheng, Feixia; Ye, Xiuyun; Shi, Xulai; Lin, Zhongdong; Yang, Zuqin; Jiang, Longxiang (Frontiers in Neurology, 2019)
Background: Hyponatremia has frequently been described as a common complication associated with bacterial meningitis, though its frequency and clinical course in children with bacterial meningitis are unclear. The present study aimed to investigate the frequency, clinical characteristics and prognosis associated with pediatric hyponatremia due to bacterial meningitis. Methods: In this prospective hospital-based study, 175 children with bacterial meningitis were enrolled. We documented all participants’ symptoms and signs, laboratory and microbiological data, radiological findings, and complications that occurred during their hospital admission. Disease severity was determined using the maximum Pediatric Cerebral Performance Category (PCPC) and minimum Glasgow Coma Scale (GCS). Residual deficits were assessed using PCPC at discharge. Results: Hyponatremia (<135 mmol/l) was seen in 116 (66.4%) of the patients assessed and was classified as mild (130-135 mmol/l) in 77, moderate (125-129 mmol/l) in 26, and severe (<125 mmol/l) in 13. Hyponatremia was associated with a shorter duration of symptoms before admission, higher CSF white cell counts, and a longer duration of hospitalization. Moderate and severe hyponatremia were associated with an increase in convulsions, impaired consciousness, altered CSF protein levels, higher maximum PCPC scores, and lower minimum GCS scores. Severe hyponatremia was further associated with the development of systemic complications including shock, multiple organ dysfunction syndrome, respiratory failure requiring mechanical ventilation, and an increase in poor outcome (PCPC ≥ 2). Hyponatremia was not associated with the development of neurologic complications. Logistic regression analyses revealed that convulsions (OR 0.10, 95% CI 0.02-0.44) and blood glucose levels (OR 1.35, 95% CI 1.08-1.70) predicted severe hyponatremia. Conclusion: Hyponatremia occurred in 66.4% of the pediatric bacterial meningitis patients assessed here. Moderate and severe hyponatremia affected the severity of pediatric bacterial meningitis. Only severe hyponatremia affected the short-term prognosis of patients with pediatric bacterial meningitis. We recommend that patients with pediatric bacterial meningitis who exhibit convulsions and increased blood glucose levels should be checked for severe hyponatremia. Further studies are needed to evaluate the effectiveness of treatment of hyponatremia.